Analysis and comparision of credit risk methodologies - Leong, Kok Choong. (2008)
In 1993, the Bank for International Settlements (BIS) proposed a method by which financial market risk would be charged. The proposed methodology proved to be so unpopular that that it galvanized the trading community into trying to find a common measurement standard to measure market risk. In 1994, with the publication of the RiskMetrics Technical Document, J.P.Morgan gave the world their vision of how market risk should be managed and value-at-risk (VAR) soon became a huge success. In April 1995, the BIS formally adopted VAR as the template for calculating market risk capital. Over the four to five years that followed, market risk and VAR were on every bank's agenda.